2015
DOI: 10.1038/nrneurol.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in perinatal brain injury

Abstract: Inflammation is increasingly recognized as being a critical contributor to both normal development and injury outcome in the immature brain. The focus of this Review is to highlight important differences in innate and adaptive immunity in immature versus adult brain, which support the notion that the consequences of inflammation will be entirely different depending on context and stage of CNS development. Perinatal brain injury can result from neonatal encephalopathy and perinatal arterial ischaemic stroke, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
665
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 673 publications
(684 citation statements)
references
References 186 publications
(173 reference statements)
16
665
1
2
Order By: Relevance
“…9,31,34 Prenatal, intrapartum, and/ or postnatal infections result in inflammatory substances that have been linked to both brain injury and altered brain development in the preterm population. 58,59 In this study, we also report an association between confirmed sepsis and stunted cerebral growth. This specific finding contrasts with 2 other studies, which found no relationship between brain volumes 7 a The estimate of variance explained includes the main effects as well as 2-and 3-way interactions (not shown); all models had a P value < .001.…”
Section: Figurementioning
confidence: 64%
“…9,31,34 Prenatal, intrapartum, and/ or postnatal infections result in inflammatory substances that have been linked to both brain injury and altered brain development in the preterm population. 58,59 In this study, we also report an association between confirmed sepsis and stunted cerebral growth. This specific finding contrasts with 2 other studies, which found no relationship between brain volumes 7 a The estimate of variance explained includes the main effects as well as 2-and 3-way interactions (not shown); all models had a P value < .001.…”
Section: Figurementioning
confidence: 64%
“…3 Given their central role in the production of pro-inflammatory cytokines, reactive oxygen species, matrix metalloproteinases and other cytotoxic molecules, a number of interventions targeted at reducing microglial activation have been tested in pre-clinical models of developmental brain injuries. 1 Reactive astrogliosis also occurs subsequent to brain injuries. Like the microglial reaction, the astroglial reaction is multifaceted.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting neuroinflammation is regarded as an important contributor to the pathogenetic cascade, contributing to both the initial injury as well as to secondary neurodegeneration. 1 The majority of studies to date have focused on the production of the classic pro-inflammatory cytokines that include IL-1ß, IL-8, IL-18, TNFa and IL-6 as acute increases in these cytokines correlate with penultimate neurological impairments in children surviving perinatal brain injuries. 2 Microglial cells are the principal sentinels of the central nervous system (CNS) and they undergo a rapid transformation to an activated phenotype when the microenvironment of the brain is perturbed.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos de los genes más estudiados en la incidencia de paralisis cerebral es el gen para la interleuquina 6 (IL6) es una citoquina pleiotrópica con varias actividades para regular la inflamación, y respuestas de la fase aguda, hematopoyesis, lesión isquémica y desarrollo cerebral 41,42 . Los polimorfismos que involucran la regulación de la expresión de IL6 se han asociado a PC en su mayoría en niños con edad gestacional entre 32-36 semanas.…”
Section: Introductionunclassified